OS DESAFIOS DA MOBILIDADE ACADÊMICA PARA A GESTÃO UNIVERSITÁRIA: UM SURVEY COM GRADUANDOS DA UDESC - Monique Raupp; Marco Antônio Seifriz (Revista Gestão Universitária na América Latina, 2016)
The internationalization of Brazilian higher education has attracted the attention of academic production, by investigating trends as increasing academic mobility in different countries, the adoption of transnational curriculum matrices and the consolidation of international networks of scientific research. At the University of the State of Santa Catarina (UDESC) this process is in its early stages, creating the need to understand the impact of internationalization phenomenon in relation to university management. This study aims to identify the main challenges and difficulties encountered by undergraduate students of the School of Business and Management (ESAG), department of UDESC, to participate in an academic mobility program in foreign universities. A survey was conducted with 208 undergraduates between the years 2009 and 2013, using semi-structured interviews by digital means. The results indicate that the mobility experience is seen by the students, predominantly, as an opportunity for personal development, and the obstacles faced by the students are mostly bureaucratic, such as validating courses taken abroad and knowing the foreign documents necessary for the local registry. Regarding the university management, it is discussed the creation of a virtual instrument support with the objective of streamlining the service to students in mobility.